PENGARUH SELF CONCEPT TERHADAP PERILAKU SHOPPING ADDICTION PADA SISWA SMAN 2 BAE KUDUS - Jumanto, Ahmad; Hidayati, Richma; Kusmanto, Agung Slamet (Jurnal Muria Research Guidance and Counseling (MRGC), 2023)
Maladaptive behavior is an action that tends to have a negative impact on both psychological and physical individuals, one of which is shopping addiction. This study aims to determine the effect of individual self-concept on shopping addiction behavior where it is hoped that this research will provide an overview for guidance and counseling teachers in improving student self-concept. The collection techniques used are self-concept and shopping addiction scales. The results obtained from this study are the calculated T value of 2.680 2.042 T table, the regression coefficient value is 49.032 (+) and R Square of 0.193 means that there is a positive influence of cell concept on shopping addiction of SMAN 2 Bae Kudus students by 19.3%.